Obesity and type 2 diabetes are important risk factors underlying previously undiagnosed cirrhosis in general practice: a cross-sectional study using Transient Elastography - Harman, David J.; Ryder, Stephen D.; James, Martin W.; Wilkes, Emilie A.; Card, Timothy R.; Aithal, Guruprasad P.; Guha, Indra Neil (Wiley, 2018)
Background: Rising cirrhosis incidence and mortality in the United Kingdom has been attributed predominantly to excess alcohol consumption. However, metabolic risk factors such as type 2 diabetes and obesity may also be important. Aim: To screen at-risk individuals in general practice for undetected cirrhosis using transient elastography and study the risk factors underlying these cases. Methods: The study was undertaken in 4 general practices (adult patient population 20,868) between February 2012 and September 2014. Patients with defined risk factors for chronic liver disease (hazardous alcohol use and/or type 2 diabetes) were identified from the General Practice electronic records and invited for transient elastography. Elevated liver stiffness was defined as ≥8 kilopascals. Cirrhosis was confirmed by established histological, radiological and biochemical methods. Results: 2,368 patients were invited for transient elastography and 899/919 who attended (97.8%) had valid measurements. Of these 230 patients had elevated liver stiffness (25.6%) and 27 had cirrhosis (2.9%). Risk factors for new cirrhosis diagnoses were obesity and/or type 2 diabetes in 16 patients (59.3%), alcohol alone in 3 (11.1%) and both alcohol and obesity and/or diabetes in 8 (29.6%). Presence of cirrhosis was significantly increased in obese patients with type 2 diabetes or hazardous alcohol use compared to non-obese (odds ratio 9.4 (95% CI 2.2-40.9) and 5.6 (95% CI 1.6-19.7) respectively). Conclusions: The number of new cases of cirrhosis diagnosed clearly demonstrates that existing estimates of prevalence are likely to be gross underestimates. Obesity was an important risk factor for cirrhosis within both alcohol users and diabetics.